#TITLE_ALTERNATIVE# - WAHYUDI PURNAMA (NIM 12402009), GEMA
Seismic signal that record subsurface condition is non-stationer signal, it means data influence with wavelet and frequency that change depends on time. In the another side, atenuation influence caused by lithology makes the frequency of seismic signal decrease depends on time. To resolve this problem we have used S-Transform that can localize signyal in time domain. The one of case in seismic reflection method occured when sesimic wave through in a thin-layer (thin-bed). The respon of seismic signal are getting interferention that happened by two layers in thin layer boundary. The tunning effect produced by seismic signal interferention and we can not detect where is the top and the bottom in a thin layer. We are using Integrate method which is summation of amplitude in one trace. In fact, we can decrease tunning effect when we use Integrate but with noise 10%, we can not to identify it. Because of that problem, I try to solve with S-Transform that can enhance resolution in thin layer.